Study on graphene oxide reinforced magnesium phosphate cement composites. (12th December 2022) - Fan, Yufeng; Zhang, Guosheng; Li, Yue
Highlights: The optimum dosage of graphene oxide in magnesium phosphate cement was found. The effect of graphene oxide addition on the hydration, microstructure and mechanical properties of magnesium phosphate cement was presented. The interaction mechanism between graphene oxide and magnesium phosphate cement was discussed. Abstract: Graphene oxide (GO) is an excellent nano reinforcing material. This paper presents the effect of GO addition on the hydration, microstructure and mechanical properties of magnesium phosphate cement (MPC). MPC with GO contents of 0.00, 0.02, 0.04, 0.06, 0.08 and 0.10 % was prepared. The functional groups, mechanical properties, phase composition and reinforcement mechanism of the GO-MPC composites were tested and analysed. The results showed that water adhered to the GO, which led to a decrease in the fluidity of the MPC paste. With increasing GO content, the most probable pore size of MPC first decreased and then increased. By adding 0.04 % GO, the most probable aperture of MPC was reduced from 11.3 μm to 0.9 μm. The proper addition of GO could refine the pore size, densify the microstructure and improve the mechanical properties of MPC. An appropriate dosage of GO promoted the hydration of MPC, resulting in more hydration products, including potassium magnesium phosphate hexahydrate (MKP), better growth of MKP with higher crystallinity.